2009
DOI: 10.1016/j.apmr.2008.07.025
|View full text |Cite
|
Sign up to set email alerts
|

Timed Walking Tests Correlate With Daily Step Activity In Persons With Stroke

Abstract: The 6MWT has the strongest relationship with the StepWatch outputs and may be a better test than the 10MWT to predict usual walking performance. However, it should be remembered that the 6MWT explains only half the variability in usual walking performance. Thus, activity monitoring captures aspects of walking performance not captured by other clinical tests and should be considered as an additional outcome measure in stroke rehabilitation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
71
3

Year Published

2010
2010
2021
2021

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 95 publications
(76 citation statements)
references
References 36 publications
2
71
3
Order By: Relevance
“…The correlation between comfortable gait speed and physical activity in the current study was similar to values reported previously [6,7,11]. In contrast, the correlations between scores on the 6MWT and BBS and physical activity in the current study were substantially weaker than previous estimates [6][7][8]11] and non-significant.…”
Section: Discussioncontrasting
confidence: 54%
See 4 more Smart Citations
“…The correlation between comfortable gait speed and physical activity in the current study was similar to values reported previously [6,7,11]. In contrast, the correlations between scores on the 6MWT and BBS and physical activity in the current study were substantially weaker than previous estimates [6][7][8]11] and non-significant.…”
Section: Discussioncontrasting
confidence: 54%
“…In contrast, the correlations between scores on the 6MWT and BBS and physical activity in the current study were substantially weaker than previous estimates [6][7][8]11] and non-significant. In four previous studies, [6][7][8]11] participants were younger and participants' walking ability was either better (two studies) or worse (one study) compared to individuals in the current study. Moreover, the time period over which the accelerometer was worn, the placement of the accelerometer (ankle vs. thigh), and the parameter used to estimate physical activity (step/activity counts vs. time spent upright) varied across studies making it difficult to compare results.…”
contrasting
confidence: 55%
See 3 more Smart Citations